Texts used in the English language arts classroom of an American Islamic school - Firman Parlindungan; Adrian Rodgers (Studies in English Language and Education, 2022)
In this article, we examine what texts were selected for use by a middle school language arts teacher working in an American Islamic school. The literature has found that schools play an important role in supporting immigrant students to navigate a new culture, especially by selecting and providing appropriate texts for learning. Since students’ interaction with texts can mediate knowledge and identity construction, what cultural information and whose culture is embedded in the texts matter for language learning. As such, we wondered what texts a teacher would use to bridge the minority culture of the students with the majority culture in which the students lived. One teacher’s language arts class with 20 students at one American Islamic school was observed for one academic quarter and then described using a case study method. We qualitatively analyzed classroom observations, field notes, teacher interviews, and teacher and student work samples. We found that the teacher was able to use both academic texts, virtual texts, and teacher-created documents to explore some of the issues that the students face on a daily basis. This study further adds to the existing knowledge that culturally relevant texts may mediate students’ understanding of the larger socio-historical contexts in which they reside including a chance to develop language skills necessary for communication and learning.